Antioxidant and haemolytic activities of Senecio species used in traditional medicine - Lizarraga, Emilio Fernando (2011)
Senecio nutans Sch. Bip., Senecio spegazzinii Cabrera and Senecioviridis Phil. var. viridis are native species used in traditional medicinein northwestern Argentina. The aerial parts of these herbs areusually used as infusion or decoction. In the present work, the totalphenolic, flavonoids and caffeoylquinic acids contents, radical scavenging(DPPH?), antioxidant (β-carotene / linoleic acid bleachingmethod) and haemolytic activities of infusions and decoctions ofthe three species above were determined. Both the decoction andthe infusion of S. nutans exhibited the highest content of phenoliccompounds, repectively: 25.2 and 20.5 mg of gallic acid equivalents(GAE) per gram of plant material (gpm); flavonoids: 7.1 and8.7 mg of quercetin equivalents (QE)/gpm and caffeoylquinic acids:18.6 and 15.9 mg of chlorogenic acid equivalents (CAE)/gpm.They also showed a higher radical scavenging activity than S. viridisvar. viridis and S. spegazzinii. The three species were very effectiveas antioxidants in the b-carotene bleaching assay with inhibitionpercentages above 65% at 47 ppm (BHT produced 94% inhibitionat 47 ppm). The extracts did not show haemolytic activity onhuman and rabbit erythrocytes.